Mastermind : how to think like Sherlock Holmes - Konnikova, Maria (Viking Adult, 2013)
"Lessons from the world's greatest fictional detective teach us how to improve our own mental powers. Konnikova unpacks mental strategies that lead to clearer thinking and deeper insights. Drawing on twenty-first century neuroscience and psychology"--